Reading Breath in Literature - Rose, Arthur; Heine, Stefanie; Tsentourou, Naya; Saunders, Corinne; Garratt, Peter (Cham Springer Nature, 2019)
This open access book presents five different approaches to reading breath in literature, in response to texts from a range of historical, geographical and cultural environments. Breath, for all its ubiquity in literary texts, has received little attention as a transhistorical literary device. Drawing together scholars of Medieval Romance, Early Modern Drama, Fin de Siècle Aesthetics, American Poetics and the Postcolonial Novel, this book offers the first transhistorical study of breath in literature. At the same time, it shows how the study of breath in literature can contribute to recent developments in the Medical Humanities.
English
Keywords: Literary theory; Literary studies: poetry & poets; Literary studies: plays & playwrights; Fiction & related items; Literature; Fiction; Drama; Poetry; Literature Philosophy